Graphene oxide-templated preferential growth of continuous MOF thin films. Issue 22 (14th December 2015) - Kim, Daeok; Coskun, Ali
Abstract : A graphene oxide film was used as an interfacial template for the preferential growth of continuous HKUST-1 films on a solid substrate. Abstract : We introduced a new strategy to fabricate defect-free continuous metal–organic framework (MOF) films using graphene oxide (GO) as an interfacial template on solid substrates. The unprecedented formation of a one-dimensional nanorod-shaped crystalline intermediate phase on the GO surface enabled the preferential growth of HKUST-1 films in the <220> direction.